Morphology and phylogeny identify two new species and one new subspecies of Podoscypha from Yunnan Province, Southwest China - Si, Jing; Zhang, Yi-Zhe; Liang, Jia-Qi; Li, Hai-Jiao (Frontiers in Microbiology, 2023)
In this study, Podoscypha was taxonomically and phylogenetically evaluated. Five specimens collected from tropical areas of Yunnan Province in Southwest China were studied. In combination of morphological observations and phylogenetic analyses based on ITS and LSU loci, two new species and one new subspecies: Podoscypha subinvoluta, P. tropica, and P. petalodes subsp. cystidiata, respectively, were discovered. Illustrated descriptions of the new species and subspecies are provided. Moreover, the main morphological differences between related species are discussed.